Alleviating the Woolliness of 'Yumyeong' Peaches by MA Packaging and the Related Properties of Pectic Substances - Choi, J.H. (Korea Food Research Institute, Seongnam, Republic of Korea), E-mail: choijh@kfri.re.kr; Lee, S.K. (Seoul National University, Seoul, Republic of Korea); Hong, Y.P. (National Horticultural Research Institute, RDA, Suwon, Republic of Korea); Hong, J.H. (Glonet BU, Doosan Corporation, Yongin, Republic of Korea) (Weon'ye gwahag gi'sulji, 2008)
Effect of modified atmosphere (MA) packaging on the woolliness and related physiological properties was investigated in 'Yumyeong' peach (Prunus persica) fruits. Harvested fruits were packaged with PE film (30 ㎛ thickness), chilled at 0℃ for 4 weeks to induce chilling injury, woolliness, and then ripened at 20℃ Changes in woolliness, electrolyte leakage, pectic substances, and the activities of polygalacturonase (PG) and pectin methylesterase (PME) were evaluated during ripening. Woolliness developed during ripening period after chilling regardless of MA packaging; however, less woolliness was found in MA-chilled fruits. Electrolyte leakage increased rapidly during the first 3 days of ripening and then decreased in chilled fruits, and was higher in MA-chilled fruits. In non-chilled fruits, water soluble pectin (WSP) content increased, EDTA soluble pectin (ESP) content remained constant, and sodium carbonate soluble pectin (SSP) contentdecreased during ripening. Chilled fruits showed inhibited PG activity, lower WSP content, and higher SSP content than non-chilled fruits, which is likely to be a cause of woolliness. In MA-chilled fruits, PME and PG activity increased, WSP increased, and SSP decreased during ripening compared with chilled fruits without MA packaging. We could conjecture that woolliness of 'Yumyeong' peach fruits could be alleviated by MA packaging in which the effect of cold storage on the PG activity might be reduced.